Seasonal aerobic performance variations in elite soccer players - Kalapotharakos, V. I.; Ziogas, G.; Tokmakidis, S. P. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to examine the seasonal changes in body composition and aerobic performance in elite soccer players. Twelve elite professional soccer players (aged 25 ± 5 years, weight 75.7 ± 5.3 kg, height 1.79 ± 0.06 m) were measured for body fat (%), maximum oxygen consumption (Vo2max), running velocity at Vo2max (vVo2max), running velocity at a fixed blood lactate concentration of 4 mmol/L (v-4 mM) at the start of the preseason period, at the beginning of the competitive period, and at midseason. Vo2max, v-4 mM, and vVo2max increased significantly (p < 0.05) by 4.5, 10.5, and 7.8, respectively, after the preseason period. Thereafter, the aerobic performance parameters remained relatively constant, with no significant changes throughout the competitive period. The results of this study suggest that moderate improvements were observed in Vo2max, and the %Vo2max at 4 v-4 mM, whereas higher improvements were observed in vVo2max and v-4 mmol/L after the preseason training period. On the other hand, during the competitive period, aerobic performance remained unchanged. In addition, this study suggests that heart rate, lactate, Vo2, and vVo2max are useful and practical predictors that help monitor aerobic performance changes during a soccer season.